Exchange Rate Shocks and the Effectiveness of Macroeconomic Policies in Malaysia - Aliasuddin (2009)
The 1997-1998 financial crises had significantly affected the East Asian countries including Malaysia. The economic growth during the crises was very low and several quarters experienced negative growth compared to the pre--crisis period. The slower economic growth caused lower income and higher unemployment because producers tried to decrease their productions due to the lower demand during the crises. The government tried to stabilize the economy by implementing some policies such as higher interest rate as a monetary policy instrument. However, the policies were not so effective to stabilize the crises because the economy recovered only after two years. Using quarterly data for the period 1980.1-2002.4, a structural vector autoregressive (SVAR) model is utilized in the study. There are eleven variables are used in the study, where five of them are exogenous variables, whereas others are endogenous ones. So, the structural equations in the study are saving deposit rate and hereafter denoted as saving interest rate, lending interest rate, government expenditure, foreign income, exchange rate, money demand, consumption, investment, exports, imports, and income. The SVAR is used because it can examine the exchange rate effects on the macroeconomic variables as well as the role of monetary and fiscal policies on the exchange rate. The SVAR also produces two important tools, forecast error variance decomposition and impulse response function. Impulse response function is used to analyze the effects of exchange rate shocks on the macroeconomic variables and the effectiveness of macroeconomic policies, whereas forecast error variance decomposition is used to analyze the sources of fluctuations of macroeconomic variables. The fluctuations of exchange rate are mainly influenced by own shocks and foreign income. Foreign income has important role because most of the exported goods are sold in the international market. There are two variables that influence the money demand, exchange rate and saving interest rate. This means that exchange rate has important role on the money demand. People consider the exchange rate in their money demand besides saving interest rate. The fluctuations of investment are dominantly determined by exchange rate shocks and saving interest rate shocks. Again, the exchange rate is so important in the investment decision, although interest rate is an important factor. There are two shocks that determine the fluctuations of imports, exchange rate and saving interest rate. Saving interest rate has power to influence the imports because most of Malaysians use credit to buy goods and services. So, interest rate is very crucial in the demand for imported goods and services. The fluctuations of income are dominantly influenced by foreign income. This means that any fluctuation in the economic is caused by outside factor. Exchange rate fluctuation can be minimized by implementing monetary and fiscal policies. However, the monetary and fiscal policies are not effective to stabilize the exchange rate fluctuations because the fluctuations come from outside of the economy.